2017
DOI: 10.1007/s00894-017-3217-z
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic progression in the free radical addition reaction: modeling, geometry, energy, and kinetics

Abstract: The free radical addition reaction is very important in UV curing. The benzoyl radical is the most commonly observed radical. In the addition process, the benzoyl radical adds to an acrylate monomer, forming a primary radical that has great value for subsequent research. In this article, a quantum chemical method was used to study the microscopic progression from the reactive complex to the saddle point. The reactions of three monomers (amylene, allyl methyl ether and methyl acrylate) with a benzoyl radical we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We believe that polymerization will still proceed quickly to yield a hemostatic effect, as confirmed in the following animal experiment. The mechanism of the free radical addition has been thoroughly investigated by our group elsewhere 14 .…”
Section: Resultsmentioning
confidence: 99%
“…We believe that polymerization will still proceed quickly to yield a hemostatic effect, as confirmed in the following animal experiment. The mechanism of the free radical addition has been thoroughly investigated by our group elsewhere 14 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, to initiate, vinyl ether requires iodonium or sulfonium salts, and the reaction proceeds via cationic polymerization. Our quantum chemistry calculation showed (Figure S1) that when a benzoyl radical from photocleavage of HMPP is added onto the double bond of AME, the addition rate constant ( k ) in the gas state is 4.6 × 10 –21 , one thousand times slower than k for addition to acrylate (2.2 × 10 –18 ) . However, in a previous study, we observed that SAE polymerization proceeded at a fairly rapid rate and formed a stable polymer, a phenomenon that is difficult to explain using the traditional FRA polymerization mechanism.…”
Section: Resultsmentioning
confidence: 82%
“…The geometric structures of LA and IDA molecules are optimized through the B3LYP function by Materials Studio, then the charge distribution is computed, and the possible reaction sites are analyzed. For different reaction modes that may occur at different sites, their transition states and energy barriers are calculated and searched, respectively, which provides a theoretical basis for the synthesis process, as well as the structure and performance analysis ( Lu and Manzetti, 2014 ; Gorantla and Mallik, 2020 ; Zhang et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%